Aśoka kī dharmalipiyām̐ - Ojhā, Gaurīśaṅkara Hīrācanda, 1863-1947; Dāsa, Śyāmasundara, 1875-1945 (Devīprasāda aitihāsika pustakamālā ;, 1923)
Study and interpretation of the inscriptions of edicts issued by Aśoka, King of Magadha, fl. 259 B.C.